Destructive Fishing Practices - Asri, Muh.; Wahyuni, Ekawati Sri; Satria, Arif (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
The objective of this study is to find out and explain the destructive fishing practices occurred in Taka Bonerate National Park area and the factors that caused it. Data retrieval was conducted with in-depth interview techniques, literature studies and documents. The results showed that destructive fishing practices were still prevalent in the Taka Bonerate National Park area, both using chemicals (cyanide) and those using explosives (bombs) in fishing activities. The conclusions from this study are that fisheries destructive activities are generally not carried out individually but in groups, namely 3-4 people led by a captain. There are several contributing factors to the proliferation of destructive fishing practices in the small islands of Taka Bonerate National Park. Where they are still under guarded, and the conflicts of authority among the Taka Bonerate National Park management authorities, conflicts between fishermen, and availability of bombs and cyanides raw materials. The other are strong position of retainer and weak position of mustard in patron client relations between punggawa-sawi. The last factor but not least, that there are markets for them to sell the bombs and cyanide fishing.